EMPOWERING ECONOMIC RESILIENCE THROUGH ECONOMIC INTELLIGENCE OPTIMIZATION - Alifah Kusumaningrum; Saparuddin Mukhtar; Dwi Ringga Edwid Dian Negara; Yeti Lastuti; Hanif Afif Naufal; Lathiefah Rabbaniyah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
In the face of uncertain global dynamics, national economic resilience has become a strategic issue that demands a response based on accurate data and information. This study aims to explore the relationship between Economic Intelligence (EI) and Economic Resilience (ER) and to formulate a strategy for optimizing EI as a proactive instrument in mitigating economic risks. Using an exploratory qualitative approach through a systematic literature review, this study analyzes various scientific sources and official institutional reports related to the role of EI in strengthening economic resilience, particularly in Indonesia. The results indicate that optimizing EI plays a crucial role in early crisis detection, supporting evidence-based policymaking, and increasing the resilience of micro, small, and medium enterprises (MSMEs) to economic shocks. However, EI implementation still faces various obstacles such as low data literacy, limited technological infrastructure, and the lack of integration of cross-institutional information systems. Therefore, a comprehensive strategy is needed that encompasses strengthening data infrastructure, developing human resource capacity, reforming data regulations, and intersectoral collaboration. This study provides a conceptual contribution to the development of an EI and ER framework and offers policy recommendations to support resilient, inclusive, and sustainable economic development.